Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika dengan Alat Peraga Gelas Variabel bagi Siswa SMPN 3 Kayangan - Maulidi, Ahmad (Jurnal Paedagogy, 2022)
This study aims to improve student activity and learning outcomes on the subject matter of linear equations with one variable with the help of variable glass props through STAD Type Cooperative learning for students of SMPN 3 Kayangan, North Lombok Regency. This research method uses classroom action research with qualitative and quantitative approaches, which are carried out in 2 cycles. Each cycle consists of stages of implementation, giving action, observation, and reflection. The subjects of this study were students of class VII.2 SMPN 3 Kayangan, totaling 33 students. Data collection techniques used observation sheets and tests were then analyzed descriptively qualitatively and quantitatively. The results of this study indicate that the increase in student learning outcomes in the first cycle obtained mastery learning reached 54.55% with an average value of 64.45. In the second cycle, the learning completeness was obtained by 66.7% with an average value of 66.6. From the results of this study, it was concluded that the STAD Type Cooperative approach learning could increase the activity and learning outcomes of class VII.2 students of SMP Negeri 3 Kayangan, North Lombok.